2009
DOI: 10.2337/dc09-0574
|View full text |Cite
|
Sign up to set email alerts
|

Are Metabolically Normal but Obese Individuals at Lower Risk for All-Cause Mortality?

Abstract: OBJECTIVEThe clinical relevance of the metabolically normal but obese phenotype for mortality risk is unclear. This study examines the risk for all-cause mortality in metabolically normal and abnormal obese (MNOB and MAOB, respectively) individuals.RESEARCH DESIGN AND METHODSThe sample included 6,011 men and women from the Third National Health and Nutrition Examination Survey (NHANES III) with public-access mortality data linkage (follow-up = 8.7 ± 0.2 years; 292 deaths). Metabolically abnormal was defined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
140
6
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(157 citation statements)
references
References 13 publications
9
140
6
2
Order By: Relevance
“…In accord with our findings, despite inconsistencies in the definitions of MH, the majority have found CVD risk to not be increased in MH OB compared with MH NW individuals (18,26,29,32,33,34,35), or have found CVD risk to be lower in MH OB compared with MUH OB (36), but not all studies agree (10). Moreover, several studies have found evidence for increased risk in MH OB compared with MH NW individuals in studies with >15 years follow-up (17,19,37).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In accord with our findings, despite inconsistencies in the definitions of MH, the majority have found CVD risk to not be increased in MH OB compared with MH NW individuals (18,26,29,32,33,34,35), or have found CVD risk to be lower in MH OB compared with MUH OB (36), but not all studies agree (10). Moreover, several studies have found evidence for increased risk in MH OB compared with MH NW individuals in studies with >15 years follow-up (17,19,37).…”
Section: Discussionsupporting
confidence: 76%
“…The question then arises, how many, if any, of the criteria may be allowed to be present before MH can be excluded? Previous studies of MHO employing similar criteria have allowed none (4,12,15), ≤1 (10,11,16,17) or ≤2 (18,19,20,21). In the present analysis, in the full dataset before exclusions (see below), each of the five risk factors was confirmed as a predictor of CVD and total mortality in univariate Cox proportional hazards models, unadjusted for any factors that might influence variation in risk factor levels.…”
Section: Definition Of Metabolic Healthmentioning
confidence: 55%
See 1 more Smart Citation
“…Three prospective studies observed that metabolically healthy obese persons have a risk of cardiovascular disease, mortality, and all‐cause mortality similar to that of metabolically healthy nonobese persons 18, 41, 42. In contrast, 2 other studies suggested that, compared with metabolically healthy nonobese persons, metabolically healthy obese persons have a higher risk of cardiovascular mortality and all‐cause mortality 16, 17. More recently, Ortega et al showed that when accounting for fitness, cardiovascular risk was lower for metabolically healthy obese persons compared with metabolically unhealthy obese persons 19.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolically healthy obese persons are characterized by having excessive body fat while displaying a favorable metabolic profile characterized by high levels of insulin sensitivity; no hypertension; and a favorable lipid, inflammation, hormonal, liver enzyme, and immune profile 15. Recent studies have indicated that this healthier metabolic profile may not translate into a lower risk for mortality,16, 17 whereas other studies suggested that this population might have cardiovascular risk comparable to metabolically healthy nonobese persons 18, 19. To the best of our knowledge, the role of CRP in the assessment of CHD risk has not been described previously in metabolically healthy obese persons.…”
Section: Introductionmentioning
confidence: 99%